Microbial strategies for techno-economic biofuel production - Srivastava, Neha 1981-; Srivastava, Manish 1973- (Clean energy production technologies, 2020)
Biofuels are one of the most sustainable options when it comes to renewable energy sources to replace fossil fuels. Biotechnological processes, such as microbial fermentation, are used to produce energy from waste biomass by converting organic substrates into biofuels. This book discusses practices to improve and enrich various microbial communities in order to enhance sustainable and economical biofuel production. It also evaluates various strategies to develop potential microorganisms and microbial consortia to produce highly efficient biofuels at a relatively low cost